MPIC: Molecular Prognostic Indicators in Cirrhosis Database for Clinical Context-Specific in Silico Prognostic Biomarker Validation - Yip, Shun H.; Fujiwara, Naoto; Burke, Jason; Shetler, Anand; Peralta, Celina; Qian, Tongqi; Hoshida, Hiroki; Zhu, Shijia; Hoshida, Yujin (Frontiers in Genetics, 2019)
Prognostic biomarker is vital in the management of progressive chronic diseases such as liver cirrhosis, affecting 1-2% of global population and causing over 1 million deaths every year. Despite numerous candidate biomarkers in literature, costly and lengthy process of validation hampers their clinical translation. Existing omics databases are not suitable for in silico validation due to ignorance of critical factors, i.e., study design, clinical context of biomarker application, and statistical power. To address the unmet need, we have developed Molecular Prognostic Indicators in Cirrhosis (MPIC) database as a representative example of omics database tailored for prognostic biomarker validation. MPIC consists of (i) molecular and clinical database structured by defined disease context and specific clinical outcome and annotated with employed study design and anticipated statistical power by disease domain experts, (ii) bioinformatics analysis engine for user-provided gene-signature- or gene-based prognostic prediction, and (iii) user interface for interactive exploration of relevant clinical cohort/scenario and assessment of significance and reliability of the result for prognostic prediction. MPIC assists cost-effective prognostic biomarker development by facilitating the process of validation, and will transform the care of chronic diseases such as cirrhosis. MPIC is freely available at www.mpic-app.org. The website is implemented in Java, Apache, and MySQL with all major browsers supported.